2023
DOI: 10.1002/pul2.12209
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Hispanic patient population with pulmonary arterial hypertension: An application of common risk stratification models

Abstract: Pulmonary arterial hypertension (PAH) is a cardiovascular disease with high mortality rate. Current guidelines propose initiation and escalation of PAH‐targeted treatment based on a goal‐directed approach targeting hemodynamic, functional, and biochemical variables. This approach has been successfully validated in large Caucasian cohorts. However, given the low number of Hispanic patients enrolled in large PAH trials and registries, it is unknown if the same prognostic tools can be applied to this patient popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our study also found that studies conducted in Europe showed lower mortality than those in the America. This could be attributed to a multitude of factors related to healthcare infrastructure, treatment availability and patient demographics 26 28–31. Cultural and socioeconomic factors may also play a role in these disparities and impact the overall healthcare-seeking behaviour of individuals in different regions 31–34…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that studies conducted in Europe showed lower mortality than those in the America. This could be attributed to a multitude of factors related to healthcare infrastructure, treatment availability and patient demographics 26 28–31. Cultural and socioeconomic factors may also play a role in these disparities and impact the overall healthcare-seeking behaviour of individuals in different regions 31–34…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Hispanics free of known cardiovascular disease have a higher RV mass and RV end-diastolic volume at baseline than other ethnicities [6]. Moreover, Hispanic patients with PAH appear to have a survival benefit compared to other PAH ethnicities [7,8]. However, the extent, validity, and potential reasons for this survival advantage remain unclear.…”
Section: Introductionmentioning
confidence: 99%